A Review of Rational Pharmacotherapy in the Use of Antibiotics in Hospitals - Haruna, Nadyah; Syakir, Darmawansyih; Nilawati, Andi (Indonesian Journal Publisher, 2026)
This study aims to examine the rational pharmacotherapy of antibiotic use in hospital settings, focusing on patterns, determinants, and the role of antimicrobial stewardship (AMS) in optimizing therapeutic outcomes. Employing a qualitative descriptive design through a literature review, this research synthesized findings from scientific journals, official reports, and academic studies published between 2015 and 2025. Data collection involved systematic literature tracing and document analysis, while the data analysis process consisted of thematic identification, data reduction, categorization, and inductive interpretation. The results reveal that the rationality of antibiotic use in Indonesian hospitals remains low, ranging between 6.67% and 68.03%, with key issues involving inappropriate antibiotic selection, incorrect dosing, and inadequate therapy duration. Limited AMS implementation and minimal pharmacist involvement were identified as major contributing factors. Conversely, evidence demonstrates that multidisciplinary AMS programs, particularly those led by clinical pharmacists, significantly improve prescribing rationality, reduce resistance rates, and lower healthcare costs. The findings provide a comprehensive understanding of how institutional, behavioral, and policy factors influence rational antibiotic use, offering implications for both clinical practice and healthcare policy reform. In conclusion, the study underscores the need for sustained AMS integration, pharmacist empowerment, and standardized evaluation systems to strengthen rational pharmacotherapy and combat antimicrobial resistance.